Pengaruh Intensitas Hujan Terhadap Erosi pada Lahan Sekitar Rawa Singkil di Desa Pondok dan Desa Parangjoro Grogol Sukoharjo Jawa Tengah - Romizah, Hafidz; Yudono, Andi Ade Renata; Wicaksono, Aditya Pandu (Indonesian Journal Publisher, 2023)
: Rawa Singkil is a former river-lake formed in Pondok and Parangjoro Village, Grogol District, Sukoharjo Regency, Central Java Province due to the straightening of the Bengawan Solo river. Land use and the buildings construction around Rawa Singkil ignore the regulations and river strips. Erosion around Rawa Singkil has the potential to cause siltation. Siltation can reduce the capacity of Rawa Singkil as a reservoir for rainwater runoff to prevent overflow flooding. This study was conducted to calculate the amount of erosion rate, Erosion Hazard Level (EHL) and the effect of rainfall intensity on erosion in Rawa Singkil. The stick method is used to measure the rate of erosion while the intensity of rainfall is measured actually based on the volume and duration of rain using a simple observatory-type rain measuring device. The results showed the largest erosion and EHL in LP-2, LP-3, LP-8, LP-9, and LP-11 respectively, namely: 438.826 tons / Ha / year Weight EHL (BIII); 62,255 tonnes/Ha/year medium EHL (S II); 447,681 tons/Ha/year weight EHL (B III); 57,025 tons/Ha/year light EHL (R I); 488,628 tonnes/Ha/year Very heavy EHL (SB IV). Correlation and regression tests indicate that rainfall intensity and rain duration specifically affect erosion rates